Soup Kitchens in Cluj-Napoca in 1817 - KÁRPÁTI, Attila István (Studia Universitatis Babeș-Bolyai Historia, 2025)
The great famine in Transylvania between 1813 and 1817 had a great effect on the economy and society. The rising number of the starving people and the consequences of the famine demanded actions from the Transylvanian Gubernium and put the municipalities under great pressure. One of the solutions to provide food for the starving people was the Rumford soup. The paper examines the question of how the Cluj-Napoca city administration and the local population tried to curb the famine and discusses the establishment and operation of soup kitchens in Cluj-Napoca in the final year of the famine. Rezumat: Marea foamete din Transilvania dintre anii 1813-1817 a avut urmări majore pentru economie și societate. Creșterea numărului de oameni înfometați și consecințele foametei au pretins acțiuni din partea Guberniului din Transilvania și au pus orașele sub mari presiuni. Una din soluțiile pentru asigurarea hranei oamenilor înfometați a fost „supa Rumford”. Lucrarea examinează modul în care administrația orașului Cluj-Napoca a încercat să diminueze foametea și discută crearea și modul de operare a „bucătăriilor pentru supă” în Cluj-Napoca în ultimul an al Foametei. Cuvinte-cheie: Cluj-Napoca, foamete, supa Rumford, „bucătărie de supă”, Miklós Wesselényi